Genome‐wide population affinities and signatures of adaptation in hydruntines, sussemiones and Asian wild asses - Jianfei Pan; Xuexue Liu; Mateusz Baca; Laure Calvière‐Tonasso; Stéphanie Schiavinato; Loreleï Chauvey; Gaétan Tressières; Aude Perdereau; Jean‐Marc Aury; Pedro H. Oliveira; Patrick Wincker; Aida Abdykanova; et al. (Molecular Ecology, 2024)
The extremely rich palaeontological record of the horse family, also known as equids, has provided many examples of macroevolutionary change over the last ~55 Mya. This family is also one of the most documented at the palaeogenomic level, with hundreds of ancient genomes sequenced. While these data have advanced understanding of the domestication history of horses and donkeys, the palaeogenomic record of other equids remains limited. In this study, we have generated genome‐wide data for 25 ancient equid specimens spanning over 44 Ky and spread across Anatolia, the Caucasus, Central Asia and Mongolia. Our dataset includes the genomes from two extinct species, the European wild ass, Equus hydruntinus , and the sussemione Equus ovodovi . We document, for the first time, the presence of sussemiones in Mongolia and their survival around ~3.9 Kya, a finding that should be considered when discussing the timing of the first arrival of the domestic horse in the region. We also identify strong spatial differentiation within the historical ecological range of Asian wild asses, Equus hemionus , and incomplete reproductive isolation in several groups yet considered as different species. Finally, we find common selection signatures at ANTXR2 gene in European, Asian and African wild asses. This locus, which encodes a receptor for bacterial toxins, shows no selection signal in E. ovodovi , but a 5.4‐kb deletion within intron 7. Whether such genetic modifications played any role in the sussemione extinction remains unknown.

Sea surface temperature reconstruction in the Pacific Ocean using multi-elemental proxy in Porites and Diploastrea corals: Application to Palau Archipelago - Marine Canesi; Eric Douville; Paolo Montagna; Louise Bordier; Sandrine Caquineau; Edwige Pons-Branchu; Guillaume Iwankow; Jarosław Stolarski; Denis Allemand; Serge Planes; Clémentine Moulin; Fabien Lombard; et al. (Chemical Geology, 2024)

Tracking population structure and phenology through time using ancient genomes from waterlogged white oak wood - Stefanie Wagner; Andaine Seguin‐Orlando; Jean‐Charles Leplé; Thibault Leroy; Céline Lalanne; Karine Labadie; Jean‐Marc Aury; Sandy Poirier; Patrick Wincker; Christophe Plomion; Antoine Kremer; Ludovic Orlando (Molecular Ecology, 2024)
Whole genome characterizations of crop plants based on ancient DNA have provided unique keys for a better understanding of the evolutionary origins of modern cultivars, the pace and mode of selection underlying their adaptation to new environments and the production of phenotypes of interest. Although forests are among the most biologically rich ecosystems on earth and represent a fundamental resource for human societies, no ancient genome sequences have been generated for trees. This contrasts with the generation of multiple ancient reference genomes for important crops. Here, we sequenced the first ancient tree genomes using two white oak wood remains from Germany dating to the Last Little Ice Age (15th century CE, 7.3× and 4.0×) and one from France dating to the Bronze Age (1700 BCE, 3.4×). We assessed the underlying species and identified one medieval remains as a hybrid between two common oak species ( Quercus robur and Q. petraea ) and the other two remains as Q. robur . We found that diversity at the global genome level had not changed over time. However, exploratory analyses suggested that a reduction of diversity took place at different time periods. Finally, we determined the timing of leaf unfolding for ancient trees for the first time. The study extends the application of ancient wood beyond the classical proxies of dendroclimatology, dendrochronology, dendroarchaeology and dendroecology, thereby enhancing resolution of inferences on the responses of forest ecosystems to past environmental changes, epidemics and silvicultural practices.

Subtle limits to connectivity revealed by outlier loci within two divergent metapopulations of the deep‐sea hydrothermal gastropod Ifremeria nautilei - Adrien Tran Lu Y; Stéphanie Ruault; Claire Daguin‐Thiébaut; Jade Castel; Nicolas Bierne; Thomas Broquet; Patrick Wincker; Aude Perdereau; Sophie Arnaud‐Haond; Pierre‐Alexandre Gagnaire; Didier Jollivet; Stéphane Hourdez; et al. (Molecular Ecology, 2022)
Hydrothermal vents form archipelagos of ephemeral deep‐sea habitats that raise interesting questions about the evolution and dynamics of the associated endemic fauna, constantly subject to extinction‐recolonization processes. These metal‐rich environments are coveted for the mineral resources they harbour, thus raising recent conservation concerns. The evolutionary fate and demographic resilience of hydrothermal species strongly depend on the degree of connectivity among and within their fragmented metapopulations. In the deep sea, however, assessing connectivity is difficult and usually requires indirect genetic approaches. Improved detection of fine‐scale genetic connectivity is now possible based on genome‐wide screening for genetic differentiation. Here, we explored population connectivity in the hydrothermal vent snail Ifremeria nautilei across its species range encompassing five distinct back‐arc basins in the Southwest Pacific. The global analysis, based on 10,570 single nucleotide polymorphism (SNP) markers derived from double digest restriction‐site associated DNA sequencing (ddRAD‐seq), depicted two semi‐isolated and homogeneous genetic clusters. Demogenetic modeling suggests that these two groups began to diverge about 70,000 generations ago, but continue to exhibit weak and slightly asymmetrical gene flow. Furthermore, a careful analysis of outlier loci showed subtle limitations to connectivity between neighbouring basins within both groups. This finding indicates that migration is not strong enough to totally counterbalance drift or local selection, hence questioning the potential for demographic resilience at this latter geographical scale. These results illustrate the potential of large genomic data sets to understand fine‐scale connectivity patterns in hydrothermal vents and the deep sea.

Biogeography of soil microbial habitats across France - Battle Karimi; Jean Villerd; Samuel Dequiedt; Sébastien Terrat; Nicolas Chemidlin‐Prévost Bouré; Christophe Djemiel; Mélanie Lelièvre; Julie Tripied; Virginie Nowak; Nicolas P. A. Saby; Antonio Bispo; Claudy Jolivet; et al. (Global Ecology and Biogeography, 2020)
Aim Intensive studies since the beginning of the 21st century have provided vast amounts of knowledge about soil microbial diversity at local and global scales. However, microbial habitats have been poorly investigated at large scale. This study aims to characterize soil bacterial habitats across France for the first time by integrating the description of numerous environmental factors and human activities. Location We focus on the large spatial scale of mainland France using the largest spatially explicit soil sampling set available across France (2,173 soils, area = 5.5 × 10 5 km 2 ). Major taxa studied Soil bacteria and archaea were studied by a high throughput sequencing approach targeting the V3‐V4 region of the 16S ribosomal ribonucleic acid ( rRNA ) gene directly amplified from soil DNA. Methods We applied decision tree learning and geostatistical approaches combining the abundant data on soil microbes and large‐scale environmental description in order to conduct a comprehensive analysis of soil bacterial and archaeal communities. Results We identified a complex mosaic of 16 distinct terrestrial habitats, based on soil type and management (pH, C : N ratio, land use). As for plants and animals, each habitat hosted generalist and specialist taxa and a specific interaction network directly or indirectly impacted by human activities. Main conclusions In a context of global change, our results emphasize that the policies for biodiversity and habitat conservation should now integrate soil microorganisms conceptually and technically.

An Assessment of Environmental Metabarcoding Protocols Aiming at Favoring Contemporary Biodiversity in Inventories of Deep-Sea Communities - Miriam I. Brandt; Blandine Trouche; Nicolas Henry; Cathy Liautard-Haag; Lois Maignien; Colomban de Vargas; Patrick Wincker; Julie Poulain; Daniela Zeppilli; Sophie Arnaud-Haond (Frontiers in Marine Science, 2020)

Into the bloom: Molecular response of pelagic tunicates to fluctuating food availability - Paolo Sordino; Salvatore D'Aniello; Eric Pelletier; Patrick Wincker; Valeria Nittoli; Lars Stemmann; Maria Grazia Mazzocchi; Fabien Lombard; Daniele Iudicone; Luigi Caputi (Molecular Ecology, 2020)
The planktonic tunicates appendicularians and thaliaceans are highly efficient filter feeders on a wide range of prey size including bacteria and have shorter generation times than any other marine grazers. These traits allow some tunicate species to reach high population densities and ensure their success in a favourable environment. However, there are still few studies focusing on which genes and gene pathways are associated with responses of pelagic tunicates to environmental variability. Herein, we present the effect of food availability increase on tunicate community and gene expression at the Marquesas Islands (South‐East Pacific Ocean). By using data from the Tara Oceans expedition, we show that changes in phytoplankton density and composition trigger the success of a dominant larvacean species (an undescribed appendicularian). Transcriptional signature to the autotroph bloom suggests key functions in specific physiological processes, i.e., energy metabolism, muscle contraction, membrane trafficking, and proteostasis. The relative abundance of reverse transcription‐related Pfams was lower at bloom conditions, suggesting a link with adaptive genetic diversity in tunicates in natural ecosystems. Downstream of the bloom, pelagic tunicates were outcompeted by copepods. Our work represents the first metaomics study of the biological effects of phytoplankton bloom on a key zooplankton taxon.

Expanding Tara Oceans Protocols for Underway, Ecosystemic Sampling of the Ocean-Atmosphere Interface During Tara Pacific Expedition (2016–2018) - Gabriel Gorsky; Guillaume Bourdin; Fabien Lombard; Maria Luiza Pedrotti; Samuel Audrain; Nicolas Bin; Emmanuel Boss; Chris Bowler; Nicolas Cassar; Loic Caudan; Genevieve Chabot; Natalie R. Cohen; et al. (Frontiers in Marine Science, 2019)

A gene graveyard in the genome of the fungus Podospora comata - Philippe Silar; Jean-Marc Dauget; Valérie Gautier; Pierre Grognet; Michelle Chablat; Sylvie Hermann-Le Denmat; Arnaud Couloux; Patrick Wincker; Robert Debuchy (Molecular Genetics and Genomics, 2019)

Analysis of the genomic basis of functional diversity in dinoflagellates using a transcriptome‐based sequence similarity network - Arnaud Meng; Erwan Corre; Ian Probert; Andres Gutierrez‐Rodriguez; Raffaele Siano; Anita Annamale; Adriana Alberti; Corinne Da Silva; Patrick Wincker; Stéphane Le Crom; Fabrice Not; Lucie Bittner (Molecular Ecology, 2018)
Dinoflagellates are one of the most abundant and functionally diverse groups of eukaryotes. Despite an overall scarcity of genomic information for dinoflagellates, constantly emerging high‐throughput sequencing resources can be used to characterize and compare these organisms. We assembled de novo and processed 46 dinoflagellate transcriptomes and used a sequence similarity network (SSN) to compare the underlying genomic basis of functional features within the group. This approach constitutes the most comprehensive picture to date of the genomic potential of dinoflagellates. A core‐predicted proteome composed of 252 connected components (CCs) of putative conserved protein domains (pCDs) was identified. Of these, 206 were novel and 16 lacked any functional annotation in public databases. Integration of functional information in our network analyses allowed investigation of pCDs specifically associated with functional traits. With respect to toxicity, sequences homologous to those of proteins found in species with toxicity potential (e.g., sxtA4 and sxtG ) were not specific to known toxin‐producing species. Although not fully specific to symbiosis, the most represented functions associated with proteins involved in the symbiotic trait were related to membrane processes and ion transport. Overall, our SSN approach led to identification of 45,207 and 90,794 specific and constitutive pCDs of, respectively, the toxic and symbiotic species represented in our analyses. Of these, 56% and 57%, respectively (i.e., 25,393 and 52,193 pCDs), completely lacked annotation in public databases. This stresses the extent of our lack of knowledge, while emphasizing the potential of SSNs to identify candidate pCDs for further functional genomic characterization.

New insights into global biogeography, population structure and natural selection from the genome of the epipelagic copepod Oithona - Mohammed‐Amin Madoui; Julie Poulain; Kevin Sugier; Marc Wessner; Benjamin Noel; Leo Berline; Karine Labadie; Astrid Cornils; Leocadio Blanco‐Bercial; Lars Stemmann; Jean‐Louis Jamet; Patrick Wincker (Molecular Ecology, 2017)
In the epipelagic ocean, the genus Oithona is considered as one of the most abundant and widespread copepods and plays an important role in the trophic food web. Despite its ecological importance, little is known about Oithona and cyclopoid copepods genomics. Therefore, we sequenced, assembled and annotated the genome of Oithona nana . The comparative genomic analysis integrating available copepod genomes highlighted the expansions of genes related to stress response, cell differentiation and development, including genes coding Lin12‐Notch‐repeat ( LNR ) domain proteins. The Oithona biogeography based on 28S sequences and metagenomic reads from the Tara Oceans expedition showed the presence of O. nana mostly in the Mediterranean Sea ( MS ) and confirmed the amphitropical distribution of Oithona similis . The population genomics analyses of O. nana in the Northern MS , integrating the Tara Oceans metagenomic data and the O. nana genome, led to the identification of genetic structure between populations from the MS basins. Furthermore, 20 loci were found to be under positive selection including four missense and eight synonymous variants, harbouring soft or hard selective sweep patterns. One of the missense variants was localized in the LNR domain of the coding region of a male‐specific gene. The variation in the B‐allele frequency with respect to the MS circulation pattern showed the presence of genomic clines between O. nana and another undefined Oithona species possibly imported through Atlantic waters. This study provides new approaches and results in zooplankton population genomics through the integration of metagenomic and oceanographic data.

Global patterns of pelagic dinoflagellate diversity across protist size classes unveiled by metabarcoding - Noan Le Bescot; Frédéric Mahé; Stéphane Audic; Céline Dimier; Marie‐José Garet; Julie Poulain; Patrick Wincker; Colomban de Vargas; Raffaele Siano (Environmental Microbiology, 2016)
Summary Dinoflagellates (Alveolata) are one of the ecologically most important groups of modern phytoplankton. Their biological complexity makes assessment of their global diversity and community structure difficult. We used massive V 9 18 S rDNA sequencing from 106 size‐fractionated plankton communities collected across the world's surface oceans during the T ara O ceans expedition (2009–2012) to assess patterns of pelagic dinoflagellate diversity and community structuring over global taxonomic and ecological scales. Our data and analyses suggest that dinoflagellate diversity has been largely underestimated, representing overall ∼1/2 of protistan rDNA metabarcode richness assigned at ≥ 90% to a reference sequence in the world's surface oceans. Dinoflagellate metabarcode diversity and abundance display regular patterns across the global scale, with different order‐level taxonomic compositions across organismal size fractions. While the pico to nano‐planktonic communities are composed of an extreme diversity of metabarcodes assigned to Gymnodiniales or are simply undetermined, most micro‐dinoflagellate metabarcodes relate to the well‐referenced Gonyaulacales and Peridiniales orders, and a lower abundance and diversity of essentially symbiotic Peridiniales is unveiled in the meso‐plankton. Our analyses could help future development of biogeochemical models of pelagic systems integrating the separation of dinoflagellates into functional groups according to plankton size classes.

Metagenomic 16S rDNA I llumina tags are a powerful alternative to amplicon sequencing to explore diversity and structure of microbial communities - Ramiro Logares; Shinichi Sunagawa; Guillem Salazar; Francisco M. Cornejo‐Castillo; Isabel Ferrera; Hugo Sarmento; Pascal Hingamp; Hiroyuki Ogata; Colomban de Vargas; Gipsi Lima‐Mendez; Jeroen Raes; Julie Poulain; et al. (Environmental Microbiology, 2014)
Summary Sequencing of 16S rDNA polymerase chain reaction ( PCR ) amplicons is the most common approach for investigating environmental prokaryotic diversity, despite the known biases introduced during PCR . Here we show that 16S rDNA fragments derived from Illumina‐sequenced environmental metagenomes ( mi tag s) are a powerful alternative to 16S rDNA amplicons for investigating the taxonomic diversity and structure of prokaryotic communities. As part of the T ara O ceans global expedition, marine plankton was sampled in three locations, resulting in 29 subsamples for which metagenomes were produced by shotgun Illumina sequencing (ca. 700 Gb). For comparative analyses, a subset of samples was also selected for R oche‐454 sequencing using both shotgun ( m454 tag s; 13 metagenomes, ca. 2.4 Gb) and 16S rDNA amplicon ( 454 tag s; ca. 0.075 Gb) approaches. Our results indicate that by overcoming PCR biases related to amplification and primer mismatch, mi tag s may provide more realistic estimates of community richness and evenness than amplicon 454 tag s. In addition, mi tag s can capture expected beta diversity patterns. Using mi tag s is now economically feasible given the dramatic reduction in high‐throughput sequencing costs, having the advantage of retrieving simultaneously both taxonomic ( B acteria, A rchaea and E ukarya) and functional information from the same microbial community.

Soil metatranscriptomics for mining eukaryotic heavy metal resistance genes - Frédéric Lehembre; Didier Doillon; Elise David; Sandrine Perrotto; Jessica Baude; Julie Foulon; Lamia Harfouche; Laurent Vallon; Julie Poulain; Corinne Da Silva; Patrick Wincker; Christine Oger‐Desfeux; et al. (Environmental Microbiology, 2013)
Summary Heavy metals are pollutants which affect all organisms. Since a small number of eukaryotes have been investigated with respect to metal resistance, we hypothesize that many genes that control this phenomenon remain to be identified. This was tested by screening soil eukaryotic metatranscriptomes which encompass RNA from organisms belonging to the main eukaryotic phyla. Soil‐extracted polyadenylated mRNAs were converted into cDNAs and 35 of them were selected for their ability to rescue the metal ( Cd or Zn ) sensitive phenotype of yeast mutants. Few of the genes belonged to families known to confer metal resistance when overexpressed in yeast. Several of them were homologous to genes that had not been studied in the context of metal resistance. For instance, the BOLA ones, which conferred cross metal ( Zn , Co , Cd , Mn ) resistance may act by interfering with Fe homeostasis. Other genes, such as those encoding 110‐ to 130‐amino‐acid‐long, cysteine‐rich polypeptides, had no homologues in databases. This study confirms that functional metatranscriptomics represents a powerful approach to address basic biological processes in eukaryotes. The selected genes can be used to probe new pathways involved in metal homeostasis and to manipulate the resistance level of selected organisms.

Development and functional annotation of an 11,303-EST collection from Eucalyptus for studies of cold tolerance - Guylaine Keller; Thibault Marchal; Hélène SanClemente; Marie Navarro; Nathalie Ladouce; Patrick Wincker; Arnaud Couloux; Chantal Teulières; Christiane Marque (Tree Genetics & Genomes, 2009)

Anchoring of a large set of markers onto a BAC library for the development of a draft physical map of the grapevine genome - Didier Lamoureux; Anne Bernole; Isabelle Le Clainche; Sarah Tual; Vincent Thareau; Sophie Paillard; Fabrice Legeai; Carole Dossat; Patrick Wincker; Marilyn Oswald; Didier Merdinoglu; Céline Vignault; et al. (Theoretical and Applied Genetics, 2006)